Emerging roles of HECT‐type E3 ubiquitin ligases in autophagy regulation. Issue 10 (5th September 2019) - Melino, Gerry; Cecconi, Francesco; Pelicci, Pier Giuseppe; Mak, Tak Wah; Bernassola, Francesca
Abstract : Autophagy is a conserved self‐eating process that delivers cytoplasmic material to the lysosome to allow degradation of intracellular components, including soluble, unfolded and aggregated proteins, damaged organelles, and invading microorganisms. Autophagy provides a homeostatic control mechanism and is essential for balancing sources of energy in response to nutrient stress. Autophagic dysfunction or dysregulation has been implicated in several human pathologies, including cancer and neurodegeneration, and its modulation has substantial potential as a therapeutic strategy. Given the relevant clinical and therapeutic implications of autophagy, there is emerging intense interest in the identification of the key factors regulating the components of the autophagic machinery. Various post‐translational modifications, including ubiquitylation, have been implicated in autophagy control. The list of the E3 ubiquitin protein ligases involved in the regulation of several steps of the autophagic process is continuously growing. In this review, we will focus on recent advances in the understanding of the role of the homologous to the E6AP carboxyl terminus‐type E3 ubiquitin ligases in autophagy control. Abstract : Ubiquitylation is a relevant determinant of autophagy regulation. E3 ubiquitin ligases promote the attachment of ubiquitin to target substrates. In this review, we will discuss recent evidence linking homologous to the E6AP carboxyl terminus (HECT)‐type E3 ubiquitin ligases to autophagy. Modification of substrates by HECT E3 ligases affects different steps of the autophagic process: initiation, nucleation of the phagophore, cargo selection, and autophagosome formation.